Efeito da suplementação aguda de beta alanina no desempenho de corredores fundistas - Ferreira, João Pedro de Souza (2022)
Beta alanine supplementation is one of the most used sports supplements in the world, capable of optimizing the sports performance of several modalities, mainly in individuals who perform high-intensity activities such as running. its acute effects during exercise. The objective of this work was to evaluate the effect of acute supplementation of beta alanine in amateur runners in a maximum progressive test on the track. The research included a studyrandomized, double-blind, placebo-controlled trial.With a sample of 14 individuals withages between 24.8 ± 3.8 years (body mass 65.3 ± 7.2 kg; height 171.1 ± 5.9 cm; %BF 6.8 ± 4.1; body mass index – BMI of 22.0 ± 2.0 kg•m-2) involved with street and/or track racing with at least 2 years of practice, belonging to the city of Lavras- MG. At first sight, the volunteers were randomly distributed between Beta Alanine (BA) and Placebo (PLA) condition and underwent anthropometric assessment (weight and height), body composition and familiarization with the tests. From the second visit, they were submitted to a standardized meal and 60 min later they were submitted to the maximum progressive test in two moments: PLA and BA. Variables for control during the study were: total distance covered, estimated VO2max, maximum speed, glycemia pre and post tests, food consumption, paresthesia, hand strength, HR and PSE.Were donemean ± standard deviation (SD), in addition to comparing the means, the variation delta (Δ) of the results. Analysis of the variables was performed using the T Test for two non-dependent samples for equality of means and the Levene test for equality of variances. No significant differences were observed in the analyzed variables, however, a slight improvement can be seen for the BA condition, namely, final distance covered(BA: 4288 ± 774.80 Vs PL: 4240 ± 908.19m; ), iregarding side effects, it was noted that only four of the fourteen volunteers reported tingling symptoms. When analyzing PIFC and PDFC parameters in BA and PL conditions, we did not observe statistical difference between moments for variables: HRmax, VO2max, Vmax and %Vpeak. The results of the present study, on beta alanine supplementation with an acute dose of 30mg/kg, did not interfere with the performance of runners during a maximum progressive test. However, we obtained a small trend of improvement in the BA condition in almost all the variables studied, results that could contribute to an improvement in the performance of these athletes.